PERSEPSI KUALITAS DAN CITRA MEREK DALAM MEMEDIASI PENGARUH E-WOM TERHADAP MINAT BELI - Dewi Febriyanti; Sayyida Sayyida; Alwiyah Alwiyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
In recent years, many FNB (food and beverage) innovations have emerged and developed rapidly in Southeast Asia, including Indonesia. One of the FNB businesses that is currently developing and going viral in Indonesia is Mixue. The opening of the first Mixue outlet in Sumenep Regency had an impact on the strong desire of the public to try it. The reason is, Mixue is currently being discussed in cyberspace. This research aims to analyze the influence of Electronic Word of Mouth (e-WOM) on Mixue consumers' buying interest in Sumenep Regency with perceived quality and brand image as mediating variables. The purposive sampling method produced data from 100 respondents. The data analysis method uses PLS-SEM (Partial Least Square Structural Equation Modeling). The Stimulus Organism Response (SOR) model is the basis of the conceptual framework. Findings show that e-WOM influences purchase intention, perceived quality, and brand image. Perceived quality has no effect on purchase intention, while brand image has an effect on purchase intention. The research results show that e-WOM has no effect on perceived product quality, but does influence the brand image of FNB products which are currently viral, which then influences purchase intentions.